Pengaruh Kepemimpinan Manajer dan Budaya Organisasi terhadap Kinerja Melalui Kepuasan Kerja Karyawan Bank Danamon Cabang Bogor - Romli . (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
The purpose of this study was to examine the effect of manager leadership (VK) and the corporate culture (VB) and job satisfaction (VKK) on employee performance (VKN). Data were collected using an instrument of the four variables. Instrument calibration is performed to test the validity and reliability coefficient. Validity calculated using product moment coefficient, and reliability was calculated using Cronbach Alpha coefficients. The model used in this study is a model of causality or influence relationships. To test the hypothesis that will be proposed in this study, the technique of analysis to be used is the Path Analysis. The study concluded that: 1) the variable manager leadership (VK) and the corporate culture (VB) and the job satisfaction have a direct influence on the employee performance (VKN); and 2) the variable manager leadership (VK) and the corporate culture (VB) through the job satisfaction (VKK) have an indirect effect on the employee performance (VKN).